Transcatheter Closure of Mitral Paravalvular Leak via Multiple Approaches. (2nd March 2021) - Liu, Yang; Xu, Chennian; Ding, Peng; Tang, Jiayou; Jin, Ping; Li, Lanlan; Chen, Min; Meng, Xin; Zhao, Hongliang; Yang, Jian
Abstract : Objectives . The purpose of this study was to review the experiences with transcatheter closure of mitral PVL after surgical valve replacement. Background . Transcatheter closure of paravalvular leak (PVL) is an intricate alternative to surgical closure. But it represents one of the most intricate procedures in the field of structural heart interventions, especially for patients with mitral PVL. Methods . From January 2015 through January 2019, 35 patients with mitral PVL after valve replacement underwent transcatheter closure. We reviewed the catheter techniques, perioperative characteristics, and prognosis. The median follow-up was 26 (3–48) months. Results . Acute procedural success was achieved in 33/35 (94.3%) patients. Twenty-five patients had single mitral prosthetic valve replacements; 10 had combined aortic and mitral prosthetic valve replacements previously; 28 had mechanical valves; and 7 had bioprosthetic valves. All percutaneous procedures were performed with local anesthesia except for seven transapical cases with general anesthesia. Multiple approaches were used: transfemoral, transapical, and transseptal via an arteriovenous loop. Multiple devices were deployed. There were no hospital deaths. The procedural time was 67–300 (124 ± 62) minutes. Fluoroscopic time was 17–50 (23.6 ± 12.1) minutes. The hospital stay was 5–17 (8.3 ± 3.2) days. Complications included recurrent hemolysis, residual regurgitation, acute renal insufficiency, and anemia. Twenty-seven (77.1%) patients improved by ≥1 New York Heart Association functional class at the 1-year follow-up. Conclusions . Transcatheter mitral PVL closure requires complex catheter techniques. However, this minimally invasive treatment could provide reliable outcomes and shorter hospital stays in selected patients. This trial is registered with NCT02917980 .